Antibiogram profile and phenotypic characteristics of clinical isolates of Staphylococcus aureus at Ayder Referral Hospital, Tigray, Ethiopia - Gebremariam, Teklay; Eguale, Tadesse; Belay, Tesfaye; Abula, Teferra; Engidawork, Ephrem (International Journal of Research in Medical Sciences, 2024)
Background: Staphylococcus aureus is a notorious pathogen known for its ability to form biofilms, contributing to a spectrum of infections ranging from minor skin abscesses to life-threatening bloodstream infections. The biofilm-forming capability of S. aureus complicates treatment and contributes to resistance to antimicrobial agents. This study investigates the antimicrobial susceptibility profiles and biofilm-forming capacities of clinical isolates of S. aureus. Methods: A total of 118 clinical isolates of S. aureus were collected and subjected to antimicrobial susceptibility testing using the disk diffusion method against a panel of 17 antibiotics. Biofilm formation was assessed quantitatively using the tissue culture plate (TCP) method, which categorizes biofilm production into strong, moderate, or weak/non-based on optical density measurements. Results: The results revealed a high resistance rate to ampicillin (71%), while resistance to linezolid was observed in only 2.54% of isolates. Notably, 49.15% of the isolates were identified as methicillin-resistant S. aureus (MRSA). Among the isolates, 64.4% were biofilm producers, with 64.5% of these being strong biofilm formers and 9.2% classified as weak biofilm formers. A significant correlation was found between antimicrobial resistance and biofilm formation, with 43 (74%) of the MRSA isolates being strong biofilm formers. This association underscores the challenge posed by biofilm-associated resistance in S. aureus infections. Conclusions: Strategies to combat biofilm-associated infections, including development of novel antimicrobial agents and biofilm-disrupting compounds, are urgently needed to mitigate the public health impact of S. aureus infections.